Analysis of the Direct Shear Test and Microstructure of the Lunar Soil Simulant Solidified by Sodium Silicate - Qinyong Ma; Hanyan Wang (Advances in Materials Science and Engineering)
The lunar soil is an ideal building material for future lunar base construction. In order to improve the strength of lunar soil, basalt with similar composition to lunar soil was used to simulate lunar soil due to lack of real lunar soil, and the simulated lunar soil was reinforced with sodium silicate. In order to study the direct shear mechanical properties of the simulated lunar soil by sodium silicate solidification, a series of direct shear tests and SEM microstructure tests were carried out, and the shear stress-displacement whole process curve was obtained. Influence law of mechanical characteristic parameters such as shear strength, shear deformation modulus, peak deformation and energy dissipation was studied. The results of the direct shear test show that the shear stress-shear displacement curve of the sample changes from hardening to softening with the increase of sodium silicate content. The shear strength and shear deformation modulus of simulated lunar soil increased first and then decreased. When the sodium silicate content was 5%, the shear strength and shear deformation modulus reached the maximum, which were 560 kPa and 7224 kPa, respectively. The addition of 5% sodium silicate increases the energy dissipation coefficient of the simulated lunar soil by about 12%. The microscopic test results show that the N-A-S-H gel and AFt formed by the alkali excitation and adsorption of the sodium silicate will connect the lunar soil simulant particles into a whole network structure, thereby improving the shear strength.